2021
DOI: 10.5146/tjpath.2021.01544
|View full text |Cite
|
Sign up to set email alerts
|

What would next generation sequencing bring to the diagnosis and treatment of sarcomas? a series of 20 cases, a single institutionÂ’s experience

Abstract: Objective: Soft tissue tumors comprise a small proportion of a pathologist's routine practice. Although morphology and immunohistochemistry are quite helpful for diagnosing these tumors, many require molecular tests. Fluorescence in-situ hybridization has been the most commonly used method for the detection of specific genomic alteration, but next generation sequencing (NGS) could be more informative in many ways.Here we present our targeted NGS experience on soft tissue tumors with a series of 20 cases. Mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Several previous studies on genetic mutation detection, including fusion genes in sarcoma, have been reported by NGS analysis using various genetic mutation detection panel kits. 13,17,[36][37][38][39] These studies have mainly reported data on fusion genes, genetic mutations, and gene amplification. Our current study obtained similar results for fusion genes.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies on genetic mutation detection, including fusion genes in sarcoma, have been reported by NGS analysis using various genetic mutation detection panel kits. 13,17,[36][37][38][39] These studies have mainly reported data on fusion genes, genetic mutations, and gene amplification. Our current study obtained similar results for fusion genes.…”
Section: Discussionmentioning
confidence: 99%